Increasing Regulatory T Cells With Interleukin-2 and Interleukin-2 Antibody Complexes Attenuates Lung Inflammation and Heart Failure Progression. Issue 1 (July 2016) - Wang, Huan; Hou, Lei; Kwak, Dongmin; Fassett, John; Xu, Xin; Chen, Angela; Chen, Wei; Blazar, Bruce R.; Xu, Yawei; Hall, Jennifer L.; Ge, Jun-bo; Bache, Robert J.; et al.
Abstract : Congestive heart failure (CHF) is associated with an increase of leukocyte infiltration, proinflammatory cytokines, and fibrosis in the heart and lung. Regulatory T cells (Tregs, CD4 + CD25 + FoxP3 + ) suppress inflammatory responses in various clinical conditions. We postulated that expansion of Tregs attenuates CHF progression by reducing cardiac and lung inflammation. We investigated the effects of interleukin-2 (IL-2) plus IL-2 monoclonal antibody clone JES6-1 complexes (IL2/JES6-1) on induction of Tregs, transverse aortic constriction–induced cardiac and lung inflammation, and CHF progression in mice. We demonstrated that end-stage CHF caused a massive increase of lung macrophages and T cells, as well as relatively mild left ventricular (LV) leukocyte infiltration. Administration of IL2/JES6-1 caused an ≈6-fold increase of Tregs within CD4 + T cells in the spleen, lung, and heart of mice. IL2/JES6-1 treatment of mice with existing transverse aortic constriction–induced LV failure markedly reduced lung and right ventricular weight and improved LV ejection fraction and LV end-diastolic pressure. Mechanistically, IL2/JES6-1 treatment significantly increased Tregs; suppressed CD4 + T-cell accumulation; dramatically attenuated leukocyte infiltration, including decreasing CD45 + cells, macrophages, CD8 + T cells, and effector memory CD8 + ; and reduced proinflammatory cytokine expressions and fibrosis in the lung of mice. Furthermore, IL2/JES6-1 administered before transverse aortic constriction attenuated the development of LV hypertrophy and dysfunction in mice. Our data indicate that increasing Tregs through administration of IL2/JES6-1 effectively attenuates pulmonary inflammation, right ventricular hypertrophy, and further LV dysfunction in mice with existing LV failure, suggesting that strategies to properly expand Tregs may be useful in reducing CHF progression. Abstract : Supplemental Digital Content is available in the text.